Analysis of an Eco-Epidemiological Model with Disease in the Prey and Predator - Wang, Lihong; Zhang, Fanghong; Jin, Cuncheng (International Journal of Mathematical Research, 2017)
We analyze and formulate an Eco-Epidemiological model with disease in the prey and predator, study the existence of the non-negative equilibria, obtain the sufficient conditions of locally asymptotical stability of the equilibria, then analyze the global stability of the positive equilibria.